Successful Control of Intractable Myoclonus in a Patient With Hypoxic Brain Injury After Intrathecal Baclofen Therapy: A Case Report - Lee, Geon Jae; Kim, Hyoung Seop (Brain & NeuroRehabilitation, 2022)
Myoclonus is an abrupt arrhythmic condition with shock-like movements that can be triggered by sensory stimuli, affecting the trunk or limbs during voluntary movement. Since motor symptoms are often not easily treatable, various pharmacological treatment options have been suggested. We report a case of using intrathecal baclofen (ITB) therapy in a patient with hypoxic brain injury (HBI), leading to the alleviation of myoclonus. A 29-year-old woman repeatedly presented with generalized myoclonus and multiple joint contractures at both upper and lower limbs after resuscitation. She cried during intractable myoclonus events, making it difficult for her to maintain a good sleep pattern. Due to the persistent status of multiple joint contractures and intractable myoclonus, we offered an ITB trial to control her symptoms. After ITB, her total scores on the Unified Myoclonus Rating Scale progressively improved as the doses of baclofen increased. Therefore, ITB therapy should be considered as a substantial option in the management of intractable myoclonus in patients with HBI to prevent various complications and improve the quality of life.